Coupled CFD-DEM simulation of hydrodynamic bridging at constrictions. (September 2016) - Mondal, Somnath; Wu, Chu-Hsiang; Sharma, Mukul M.
Highlights: Coupled CFD-DEM to model jamming of neutral monodisperse particulate suspensions. There exists a critical particle volume concentration ϕ* for spontaneous bridging. ϕ* depends dimensionless outlet size, inlet size and flow geometry. Jamming probability increases with flow velocity and particle-fluid density ratio. Abstract: This paper presents a coupled CFD-DEM approach to simulate the flow of particulate suspensions in the intermediate concentration regime where solid volume concentration is 1% < ϕ < 50%. In particular, hydrodynamic multi-particle bridging during flow through a single constriction in a rectangular channel is studied. It is shown that for neutrally buoyant, monodispersed particulate suspensions, the probability of jamming increases with the particle concentration. There also exists a critical particle concentration ( ϕ *) for spontaneous bridging, which depends on the ratio of pore size to particle size, the flow velocity, the particle-fluid density contrast, and the flow geometry leading to the constriction. The ϕ * has a strong dependence on the outlet-to-particle relative size ( Ro ). For 1.5 ≤ Ro ≤ 2.5, a direct transition from a flowing state to a jammed state was observed. For Ro ≥ 3, the flowing state typically transitioned to a dense state characterized by the accumulation of particles near the constriction before jamming. Increasing the inlet-to-particle relative size ( Rip ) lowers ϕ * by increasing the number of particles arriving at the constriction simultaneously. The effect of changing Rip is more pronounced at high Ro when the probability of bridging is lower. A high fluid velocity increases particle interactions near the constriction and accelerates the onset of bridging. However, no distinct effect of velocity on ϕ * was observed in this study. A higher particle-to-fluid density ratio ( ρp / ρf ) increases the probability of bridging and leads to a lower ϕ * in a given constriction geometry. The effect saturates at higher ρp / ρf when gravitational forces completely dominate over viscous drag forces. ϕ * is also found to decrease with increasing angle of constriction convergence ( θ ) for θ < 30°, but increases beyond that at θ = 60 ∘ .